This question was previously asked in

SSC CGL Tier-II ( JSO ) 2019 Official Paper ( Held On : 17 Nov 2020 )

Option 2 : P(A)

Cell

298865

10 Questions
10 Marks
7 Mins

**Explanation**

If the event B occurs does not change the probability that event A occurs, and event A and B are the independent event then

⇒ P(A I B) = P(A)

According to bayes’s theorem It states the relation between the probabilities of A and B, P(A) and P(B) and the conditional probabilities of A gives B and B gives A.

⇒ P(A I B) and P(B I A)

⇒ P(A I B) = P(B I A).P(A)/P(B)

⇒ P(B I A) = P(A ∩ B)/P(A)

⇒ P(A ∩ B) = P(A).P(B)

⇒ P(A I B) = P(A ∩ B).P(A)/P(A). P(B)

⇒ P(A I B) = P(A). P(B).P(A)/P(A).P(B)

⇒ P(A I B) = P(A)